Investigation of F and Zr Isotopes Self-Absorption and Dose Rate Parameters for PET Imaging - Abdulrahman A. Alfuraih; Khalid Alzimami; Andy K. Ma (SAGE Publishing, 2021)
This work concerns study of self-absorption factor (SAF) and dose rate constants of zirconium-89 ( 89 Zr) for the purpose of radiation protection in positron emission tomography (PET) and to compare them with those of 18 F-deoxyglucose ( 18 F-FDG). We analyzed the emitted energy spectra by 18 F and 89 Zr through anthropomorphic phantom and calculated the absorbed energy using Monte Carlo method. The dose rate constants for both radionuclides were estimated with 2 different fluence-to-effective dose conversion coefficients. Our estimated SAF value of 0.65 for 18 F agreed with the recommendation of the American Association of Physicists in Medicine (AAPM). The SAF for 89 Zr was in the range of 0.61-0.66 depending on the biodistribution. Using the fluence-to-effective dose conversion coefficients recommended jointly by the American National Standards Institute and the American Nuclear Society (ANSI/ANS), the dose rate at 1 m from the patient for 18 F was 0.143 μSv·MBq −1 ·hr −1 , which is consistent with the AAPM recommendation, while that for 89 Zr was 0.154 μSv·MBq −1 ·hr −1 . With the conversion coefficients currently recommended by the International Committee on Radiological Protection (ICRP), the dose rate estimates were lowered by 2.8% and 2.6% for 89 Zr and 18 F, respectively. Also, we observed that the AAPM derived dose is an overestimation near the patient, compared to our simulations, which can be explained by the biodistribution nature and the assumption of the point source. Thus, we proposed new radiation protection factors for 89 Zr radionuclide.